A Real-Time Egg Incubator Monitoring System with ESP32 and Blynk - Wijaya, Andi; Aini, Syarifah; Hidayat, Kemas Muhammad Wahyu (Journal of Artificial Intelligence and Software Engineering, 2025)
Poultry farming, especially chicken, contributes to the provision of world food needs, especially in the provision of chicken meat and eggs to fulfill human protein. However, the productivity of chicken farming is often hampered by traditional egg hatching methods. Egg hatching is traditionally done by the mother hen, which affects the number and quality of chicks produced. The purpose of this research is to increase the productivity of chicken farms which are often hampered by traditional methods of hatching chickens, by applying IoT (Internet of Things) Technology as a solution to more modern egg hatching methods using DHT11 sensors and Lcd 16x2 i2c as temperature and humidity monitoring. It shows that DHT1 is able to maintain temperature in the optimal range of 37°C-39°C with an average difference between DHT11 and thermometer of only 0.3°C - 0.4°C, and humidity that remains stable at a difference of 3% - 4%. The results of this study indicate that the DHT11 is accurate enough to measure air temperature in a stable environment.